A Re-assessment of the German armaments production during World War II - Salavrakos, Ioannis-Dionysios (Scientia Militaria - South African Journal of Military Studies, 2016)
The German armaments production during World War II (1939-1945) is a highly debatable issue. Many studies point out that it was a success story since the overall production increased in spite of the heavy Allied air bombing campaign during the period 1943-1945. Others point out that the size of the production could not balance the aggregate production of Britain, USA, and the USSR. This study points out that by the end of 1941 with the entry of the USSR and the US in the war Germany had to plan for two different types of war. One was a land war against the USSR and the second was a naval-air war against the Anglo-Saxon Powers (Britain and the USA). German industry did quite well with the first challenge (with the assistance of captured material and industrial power of occupied Europe) but failed in the naval-air war against the Anglo-Saxon Powers.